Guillain-Barre Syndrome Mimicked by Spinal Stenosis in A Case of Chronic Prolapsed Intervertebral Disc: A Case Report - Lee, Yi Xuan (International Journal of Medical Students, 2023)
Background: Guillain-Barre Syndrome (GBS) is a rare acute autoimmune polyneuropathy, usually preceded by infections. It can be difficult to diagnose, especially in patients with underlying neurological comorbidities. Case: A 54-year-old male, with a long history of a prolapsed intervertebral disc, presented with progressive and asymmetrical onset tetraparesthesia for 4 weeks, which was associated with progressive paraparesis for 2 weeks. The diagnosis of GBS was initially missed due to a lack of relevant history of prior infection, atypical presentation (asymmetrical limb weakness), and radiological evidence of spinal stenosis. Nerve conduction study, cerebrospinal fluid analysis, and antiganglioside antibodies later confirmed the diagnosis of GBS. The patient was started on intravenous immunoglobulin and achieved significant improvement. He was discharged a week later and transferred to a rehabilitation hospital. Conclusion: GBS should not be excluded prior to diagnostic tests and lab work in neurological patients. Physicians should avoid over-reliance on radiological findings to conclude a diagnosis. Comprehensive history and examinations to understand the development of patients' presentations should be prioritized when establishing a diagnosis.